1999
DOI: 10.1016/s0927-6505(99)00011-0
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-ray positrons: are there primary sources?

Abstract: Galactic cosmic rays consist of primary and secondary particles. Primary cosmic rays are thought to be energized by first order Fermi acceleration processes at supernova shock fronts within our Galaxy. The cosmic rays that eventually reach the Earth from this source are mainly protons and atomic nuclei, but also include electrons. Secondary cosmic rays are created in collisions of primary particles with the diffuse interstellar gas. They are relatively rare but carry important information on the Galactic propa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 23 publications
2
43
1
Order By: Relevance
“…The PAMELA data will be available shortly. Consequently, it will be possible to discriminate our speculations from others where a possible dark matter origin for positrons above a few GeV was suggested (see, in particular, Coutu et al 1999;Lionetto et al 2005;Picozza et al 2006). Finally, we expect positron observations to be consistent with those of pulsed gamma-ray measurements from the GLAST experiment that will clarify the role of electromagnetic [2006][2007] at solar minimum during a negative polarity period (φ = 550 MV/c).…”
Section: Experimental Clues On Positron Pulsar Polar Cap Originmentioning
confidence: 79%
See 1 more Smart Citation
“…The PAMELA data will be available shortly. Consequently, it will be possible to discriminate our speculations from others where a possible dark matter origin for positrons above a few GeV was suggested (see, in particular, Coutu et al 1999;Lionetto et al 2005;Picozza et al 2006). Finally, we expect positron observations to be consistent with those of pulsed gamma-ray measurements from the GLAST experiment that will clarify the role of electromagnetic [2006][2007] at solar minimum during a negative polarity period (φ = 550 MV/c).…”
Section: Experimental Clues On Positron Pulsar Polar Cap Originmentioning
confidence: 79%
“…Finally, only a reliable secondary-component evaluation leads to identifying possible extra positron sources. As an example, it was proposed in Coutu et al (1999), among other possibilities, that the feature observed above 6 GeV in the e + /(e + +e − ) HEAT data was due to supersymmetric particle annihilation. This possibility could have been ruled out in the case of the secondary calculation by Stephens was assumed (instead of the models by Protheroe or Moskalenko & Strong), as can be noticed in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(for example, Harding & Ramaty 1987;Chi et al 1996). However, Coutu et al (1999) compared these model results with the observed data and concluded that none of these models can be ruled out yet because of the uncertainties in the models and in the observed data (Coutu et al 1999). Here we will focus on the origin of cosmic ray positrons from mature pulsars.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observation with CAPRICE94 (Boezio et al 2000) shows that the observed positron spectrum and the positron fraction below about 10 GeV are consistent with a pure secondary origin in the diffusion model of cosmic ray propagation. However, the positron data at energies between 1 and 50 GeV, measured with the HEAT balloon-borne instrument (Coutu et al 1999), suggest that a small additional positron component may Send offprint requests to: L. Zhang, e-mail: lzhang@bohr.physics.hku.hk be present that cannot be explained by a purely secondary production mechanism. It should be pointed out that there is still some room for an additional positron component because of limiting statistics at high energies.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Many authors have thus studied wave propagation, plasma configuration, particle acceleration, etc., in such plasmas. [6][7][8][9][10][11][12][13][14][15][16][17][18] In a recent paper, 19 it has been shown that an oblique magnetosonic shock wave in an electron-positron-ion ͑e-p-i͒ plasma can accelerate positrons to ultrarelativistic energies. During the acceleration, these positrons stay in the shock transition region and move nearly parallel to the external magnetic field B 0 .…”
Section: Introductionmentioning
confidence: 99%